2007
DOI: 10.1177/0011128707301629
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorder in a Juvenile Assessment Center

Abstract: Juvenile assessment centers (JACs) were developed to address service fragmentation and promote the sharing of information among agencies providing services to youth involved with the juvenile justice system. To date, there are no reports that describe the diagnostic profiles of the youth served by such centers. The authors hypothesize that the rates of psychiatric disorder among youth at JAC intake would be lower than rates reported for youth in secure care, that girls would show higher rates of some disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
1
16
0
3
Order By: Relevance
“…First, the rate of mental health problems in youth arrested may be as high as in Table 2 Mental health screening, positive mental health screening rates, STI screening, and positive STI screening rates pre-and postimplementation of detention diversion for juveniles detained Ն 5 days (N ϭ 883 youth before diversion, N ϭ 746 youth after diversion) detained youth, a finding supported by previous research. Investigators explored the mental health diagnoses of arrested youth at probation intake [23,24] and found that 45% of male and 50% of female arrestees in Texas [25], and 27% and 39%, respectively, in Florida, met criteria for a mental illness diagnosis [24]. Hence, our finding supports previous research evidence that, although at rates still lower than among detained youth, arrested youth have significant psychopathology.…”
Section: Mental Health Screeningsupporting
confidence: 84%
“…First, the rate of mental health problems in youth arrested may be as high as in Table 2 Mental health screening, positive mental health screening rates, STI screening, and positive STI screening rates pre-and postimplementation of detention diversion for juveniles detained Ն 5 days (N ϭ 883 youth before diversion, N ϭ 746 youth after diversion) detained youth, a finding supported by previous research. Investigators explored the mental health diagnoses of arrested youth at probation intake [23,24] and found that 45% of male and 50% of female arrestees in Texas [25], and 27% and 39%, respectively, in Florida, met criteria for a mental illness diagnosis [24]. Hence, our finding supports previous research evidence that, although at rates still lower than among detained youth, arrested youth have significant psychopathology.…”
Section: Mental Health Screeningsupporting
confidence: 84%
“…Associations have been found between adolescent substance use and abuse with antisocial behaviour, rebelliousness, aggressiveness, crime, delinquency, truancy and school performance (Federman et al, 1997). Many studies have found high substance use among juvenile offenders (Vaughn et al, 2007;McReynolds et al, 2008;Hussey et al, 2007). We found that most of the detainees abused or were dependent to illicit drugs rather than alcohol.…”
Section: Discussionmentioning
confidence: 52%
“…A great concern in Malaysia is that most cases of drug abuse involve young people in their productive years (Rusdi et al, 2008). Apart from SUD and CD, most co-morbid disorders in this study were not statistically significant although associations between concomitant substance use and other psychiatric disorders have been well documented (Deykin et al, 1992;Greenbaum et al, 1996;McReynolds et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…Most justice youths are not incarcerated, but are managed in their communities (Snyder and Sickmund 2006). Service needs in this larger group of youth undergoing intake into the juvenile justice system, based on rates of disorder, are markedly lower than for incarcerated youths but still higher than for those in the general community (McReynolds et al 2008;Wasserman et al 2005;Wasserman and McReynolds 2006).…”
Section: Introductionmentioning
confidence: 86%